Efficacy, Immunogenicity, and Safety of the Combined Vector Vaccine Gam-COVID-Vac in Patients with Rheumatic Diseases - A. N. Kulikov; N. V. Muravyeva; B. S. Belov; G. I. Gridneva; E. S. Aronova; Z. G. Verizhnikova; E. Yu. Samarkina (Антибиотики и Химиотерапия)
The aim of the study is to assess the efficacy, immunogenicity, and safety of the combined vector vaccine Gam-COVID-Vac and to determine the risk factors for the development of adverse events (AEs) in patients with rheumatic diseases (RD).Patients and methods. The present study consisted of a retrospective and prospective parts, which included 295 and 42 patients with RD, as well as 113 and 57 healthy controls, respectively. Information about efficacy was obtained from 291 patients with RD and 146 controls, which was assessed by the incidence of PCR-confirmed COVID-19 cases from 31 to 365 days after vaccination. The concentration of antibodies to SARS-CoV-2 was assessed by enzyme immunoassay in a prospective cohort at 1, 3, 6, and 12 months after administration of the second component of the vaccine. Safety was studied in all participants based on the incidence of AEs and exacerbation of underlying RD.Results. After vaccination, 29 (9.97%) cases of COVID-19 were recorded in patients with RD, 27 of them were mild, and 2 required hospitalization, all cases ended in recovery. Treatment with rituximab before vaccination increased the risk of developing COVID-19 by 2.3 times. A sig-nificant increase in antibody titers was observed after 1, 3, and 12 months after full immunization in patients with RD (P<0.006 for all points). AEs were absent in 40.72% of patients with RD and 24.71% healthy controls, P<0.001. Exacerbations of RD were registered in 2 (0.6%) cases. The risk of developing local and systemic AEs (depending on the administered component) was increased in women, patients under the age of 60 year, with a duration of RD less than 10 years, and methotrexate therapy (P<0.016 for all cases).Conclusions. According to the data obtained, the use of Gam-COVID-Vac in patients with RD is characterized by good efficacy, sufficient immunogenicity, and safety.